Relação entre anemia e parasitoses intestinais: análise baseada em dados laboratoriais de amostras provenientes de três regiões brasileiras - Souza, Samya Fernandes de (My University, 2026)
Anemia and intestinal parasitic infections are major public health problems, especially among vulnerable populations. The objective of this study was to analyze the relationship between intestinal parasitic infections, anemia, and hematological abnormalities in individuals served by a clinical laboratory in the Serra Gaúcha region. This was an observational, cross-sectional, and retrospective study conducted using laboratory data collected between January and December 2025. A total of 13,717 individuals who underwent both a stool parasitological examination and a complete blood count were included. The data were analyzed using descriptive statistics, the chi-square test, and odds ratios. After excluding samples that tested positive exclusively for Urbanorum spp., the positivity rate for enteroparasitic infections was 0.96%. The most common parasites were Entamoeba coli (40.9%), Endolimax nana (38.6%), and Giardia lamblia (14.4%), with a predominance of protozoa. The highest prevalence of positive results was observed in the Northeast region. Considering all samples, including those with Urbanorum spp., 8.6% of individuals had hemoglobin levels below reference values, with children being the most affected group. Among individuals with positive parasitological test results, 7.9% had anemia, with no significant association between enteroparasitic infections and reduced hemoglobin levels. A slight association was observed between positivity for enteroparasites and eosinophilia. It is concluded that the prevalence of enteroparasitic infections was low, with a predominance of nonpathogenic protozoa, and no significant association with anemia, although a slight association with eosinophilia was observed. [resumo fornecido pelo autor]
A anemia e as enteroparasitoses constituem importantes problemas de saúde pública, especialmente em populações vulneráveis. Este estudo teve como objetivo analisar a relação entre enteroparasitoses intestinais, anemia e alterações hematológicas em indivíduos atendidos por um laboratório de análises clínicas da Serra Gaúcha. Trata-se de um estudo observacional, transversal e retrospectivo, realizado com dados laboratoriais obtidos entre janeiro e dezembro de 2025. Foram incluídos 13.717 indivíduos que realizaram concomitantemente exame parasitológico de fezes e hemograma. Os dados foram analisados por estatística descritiva, teste de qui-quadrado e Odds Ratio. Após a exclusão das amostras positivas exclusivamente para Urbanorum spp., a positividade para enteroparasitoses foi de 0,96%. Os parasitas mais frequentes foram Entamoeba coli (40,9%), Endolimax nana (38,6%) e Giardia lamblia (14,4%), com predominância de protozoários. A maior frequência de positividade foi observada na região Nordeste. Considerando todas as amostras, incluindo aquelas com presença de Urbanorum spp., 8,6% dos indivíduos apresentaram hemoglobina abaixo dos valores de referência, sendo as crianças o grupo mais afetado. Entre os indivíduos com exame parasitológico positivo, 7,9% apresentaram anemia, sem associação significativa entre enteroparasitoses e redução dos níveis de hemoglobina. Observou-se discreta associação entre positividade para enteroparasitas e eosinofilia. Conclui-se que a prevalência de enteroparasitoses foi baixa, com predomínio de protozoários não patogênicos, sem associação significativa com anemia, embora tenha sido observada relação discreta com eosinofilia. [resumo fornecido pelo autor]
Keywords: Parasitologia médica; Anemia; Doenças parasitárias; Eosinofilia